2017
DOI: 10.1073/pnas.1705783114
|View full text |Cite|
|
Sign up to set email alerts
|

Null effects of boot camps and short-format training for PhD students in life sciences

Abstract: Many PhD programs incorporate boot camps and summer bridge programs to accelerate the development of doctoral students' research skills and acculturation into their respective disciplines. These brief, high-intensity experiences span no more than several weeks and are typically designed to expose graduate students to data analysis techniques, to develop scientific writing skills, and to better embed incoming students into the scholarly community. However, there is no previous study that directly measures the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…One of our key findings is that faculty who have participated in informal training like workshops or boot camps report the need for training more than faculty with no training or faculty with formal training. This result is similar to that reported by Feldon et al, who suggest that boot camps and short workshops are not very effective for PhD students in the life sciences (34). Therefore, it may be useful to conduct a follow-up survey to address the deficits expressed by faculty with informal training.…”
Section: Discussionsupporting
confidence: 87%
“…One of our key findings is that faculty who have participated in informal training like workshops or boot camps report the need for training more than faculty with no training or faculty with formal training. This result is similar to that reported by Feldon et al, who suggest that boot camps and short workshops are not very effective for PhD students in the life sciences (34). Therefore, it may be useful to conduct a follow-up survey to address the deficits expressed by faculty with informal training.…”
Section: Discussionsupporting
confidence: 87%
“…SitC Annotator training is not meant to be a comprehensive course covering all aspects of DBER research. Previous work has shown that short trainings, such as this, have limited success in producing long-term changes (Schussler 2015, Feldon 2017. However, there is also evidence showing that undergraduate students who explored teaching, but did not ultimately enter the profession, retain positive and lasting changes in interest in future volunteering in public schools and in intentions to support outreach efforts in the workplace (Whang-Sayson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that short training experiences such as this have had limited success in producing longterm changes (Schussler, 2015;Feldon, 2017). This training can be seen as an "on-ramp" for students to explore DBER and is not meant to be a comprehensive course.…”
Section: Discussionmentioning
confidence: 99%
“…Research-based literature in this area cautioned us against short-term GTA training programs (3,26,27). However, the reality of academic life is that sometimes long-term training programs in the specific area of teaching are not possible for a number of reasons (3,28,29), and this is where short term-training programs, even though not ideal, can be beneficial for GTA preparation (29,30,31).…”
Section: Limitations and Recommendationsmentioning
confidence: 99%